The experience of exercise: women survivors of sexual violence - Smith-Marek, Erika Nicole (Kansas State University, 2015)
Sexual violence is pervasive in the lives of women across the globe. Survivors commonly experience a range of mental health conditions following sexual trauma, rendering the development and examination of effective treatments to be critical. Preliminary research supports the use of adjunct exercise interventions for the treatment of trauma. In order to explore the impact of exercise interventions for the treatment of sexual violence, specifically, it is necessary to first come to understand survivors’ experiences of exercise. To better understand the experience of exercise among women survivors of sexual violence, a phenomenological study, informed by a feminist perspective, was conducted with survivors of sexual violence receiving services at a rape crisis center. Data analysis uncovered four themes that capture the survivors’ experience: exercising (and avoiding exercising) fosters safety, exercising is risky, past trauma restricts exercise choices, and exercising is beneficial. Survivors’ choices related to exercise were found to be conscious and deliberate and were impacted by their stage of recovery. Implications for future research and practice are discussed.
Keywords: Exercise; Rape; Self-determination Theory; Sexual Assault; Trauma; Yoga; Individual & Family Studies (0628); Kinesiology (0575); Mental Health (0347)